FOLKTALES AND RITES OF PASSAGE IN RANDA JARRAR'S A MAP OF HOME - Hasnul Insani Djohar (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2019)
This paper examines the struggle of American-Muslim women to negotiate their identities in literary works published after the invasion of Iraq (20 March-1 May 2003). In this case, I examine Randa Jarrar’s A Map of Home (2008) in order to investigate how Jarrar both negotiates her identity through folktales, naming, and rites of passages. By engaging with postcolonial studies, and working within the frameworks of cultural studies, this paper aims to investigate aesthetic strategies that Jarrar (Egyptian-Palestinian-American) deploys in her writing. Jarrar also respects her Muslim intellectual forebears, such as Muhammad al-Ghazali (Iran), Muhyiddin al-Arabi (Spain), and Jalaluddin Rumi (Turkey), by emulating their tendency to combine in their writings allusions to the Qur’an, ancient storytelling traditions, and contemporary social issues in order to engage with their readers. In doing so, Jarrar uses folktales, naming, and rites of passages to question American belonging and eurocentrism in her fiction. These techniques enable Jarrar to reveal her multiple and complex identities and work to represent both her pride in being Muslims and her desire to claim her rights as American citizens of Muslim descent. Keywords: Randa Jarrar, A Map of Home, folktales, Rites of Passages, US-Muslim women’s literature Artikel ini membahas perjuangan perempuan Amerika-Muslim untuk menegosiasikan identitas mereka dalam karya sastra yang diterbitkan setelah invasi ke Irak (20 Maret-1 Mei 2003). Dalam hal ini, saya meneliti Randa Jarrar's A Map of Home (2008) untuk menyelidiki bagaimana Jarrar menegosiasikan identitasnya dan menentang orientalisme di sepanjang novelnya. Dengan menggunakan studi postkolonial dan studi budaya, artikel ini bertujuan untuk menyelidiki strategi estetika yang Jarrar (Mesir-Palestina-Amerika) gunakan dalam tulisannya. Jarrar juga menghormati leluhur intelektual Muslimnya, seperti Muhammad al-Ghazali (Iran), Muhyiddin al-Arabi (Spanyol), dan Jalaluddin Rumi (Turki), dengan meniru kecenderungan mereka untuk menggabungkan dalam tulisan-tulisan mereka kiasan Alquran, kuno tradisi mendongeng, dan masalah sosial kontemporer untuk menarik pembaca mereka. Dalam hal ini, Jarrar juga menggunakan dongeng, penamaan, dan ritus-ritus untuk mempertanyakan kepemilikan Amerika dan Eurosentrisme dalam fiksinya. Teknik-teknik ini memungkinkan Jarrar untuk mengungkapkan identitasnya yang beragam dan kompleks yang berfungsi untuk menunjukkan kebanggaannya sebagai Muslim dan keinginannya untuk mengklaim hak-haknya sebagai warga negara Amerika keturunan Muslim. Kata kunci: Randa Jarrar, A Map of Home, cerita rakyat, ritus peralihan, sastra Muslimah-Amerika